Trend forecast of export of cargo-carrying services of Belarus - Koroleva, Anna A.; Dutina, Alina A. (Journal of the Belarusian State University. Economics, 2018)
The article analyses the export of cargo-transportation services in 2017, makes a comparative analysis of its structure. A mathematical model that adequately describes the export of cargo-carrying transport services was built, a forecast of development of such services until 2020 has been made.